Fungicidal protection of sunflower against the main leaf diseases - S. Retman; N. Bazykina (Карантин і захист рослин)
Goal. To determine the technical efficiency of the novel fungicides against the diseases of leaves sunflower and to establish the optimal terms of fungicidal treatments for the zone of the Right Bank Forest-steppe of Ukraine.